Síntese e caracterização de pastas de cimento aditivadas com resinas epóxi análises cinéticas, termodinâmicas e calorimétricas - Tavares, Andrea Macleybiane Gois (2010)
Cement has been used in the world, presenting a wide versatility. However, due to its chemical nature, it is subject to several types of chemical damages, especially for agents of acidic nature. With the purpose of increase its life-time, new cement slurries have been modified with the addition of specific additives. The objective of this work is to modify cement slurries with epoxy resins, which promote higher resistance of those materials in relation to acid attacks. Three cement slurries were synthesized with epoxy resins (GY, PY-1 and PY-2) and a standard slurries, which was composed by cement and water (w/c = 0,5). The syntheses were performed according to the API recommendations. After 30 days of hydration, the samples were characterized by XDR, FTIR and thermal analysis (TG and DSC). The slurries characterization has suggested the presence of low amounts of portlandita (Ca(OH)2) in the slurry with the higher content of polymerized epoxy resin. The hydration processes of the cement slurries were studied by heat-conduction microcalorimetry. The energetic and enthalpic hydration data were all exothermic in nature. It was verified that the addition of the polymers delayed the processes of hydration of the slurries, decreasing the flow of heat released as a function of the amount of added resin. The cumulative heat release curves have shown the presence of multilinearity of the kinetic processes. The hydration microcalorimetric data were well fitted to the multistep Avrami kinetic model. A kinetic study of HCl interaction with the new slurries were performed by the batch methodology at 25, 35, 45 e 55°C. The Avrami kinetic model also appears to be the most efficient in describing the kinetic isotherms. It was observed that the kinetic constants of interaction of the acid with the slurries increased with the increase of temperature and decreased as a function of the amount of resin added in the slurries. The speed of reaction of the cement slurries with HCl was determined from the kinetic parameters obtained by the Avrami model. Speed reaction in the order of 10-3 mol.g.h-1 were found for the standard slurry and of the order of 10-5 mol.g.h-1 for the slurries with the epoxy resins. In general, the analysis of the kinetic parameters indicated that increasing the resin amount in the composition of the slurries reduced the reaction speed and increased the resistance of those slurries to the acid attack.